RP-18 TLC Chromatographic and Computational Study of Skin Permeability of Steroids - Anna W. Weronika Sobanska; Jeremy Robertson; Elżbieta Brzezińska (MDPI AG, 2021)
The skin permeability of steroids, as investigated in this study, is important because some of these compounds are, or could, be used in preparations applied topically. Several models of skin permeability, involving thin layer chromatographic and calculated descriptors, were generated and validated using Kp reference values obtained in silico and then tested on a group of solutes whose experimental Kp values could be found (log Kpexp). The study established that the most applicable log Kp model is based on RP-18 thin layer chromatographic data (RM) and the calculated descriptors VM (molar volume) and PSA (polar surface area). Two less efficient, yet simple, equations based on PSA or VM combined with HD (H-donor count) can be used with caution for rapid, rough estimations of compounds' skin permeability prior to their chemical synthesis.